2022
DOI: 10.1101/2022.09.15.508124
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dimethyl fumarate modulates the Duchenne muscular dystrophy disease program following short-term treatment inmdxmice

Abstract: New medicines are urgently required to treat the fatal neuromuscular disease, Duchenne muscular dystrophy (DMD). DMD involves progressive muscle damage and weakness, which are preceded by oxidative stress, inflammation, and mitochondrial dysfunction. Dimethyl fumarate (DMF) is a potent small molecule nuclear erythroid 2-related factor 2 (Nrf2) activator with current clinical utility in the treatment of multiple sclerosis and psoriasis. Pharmaceutical targeting of Nrf2 by DMF has strong translational potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 66 publications
2
12
0
Order By: Relevance
“…OCT‐covered gastrocnemius, tibialis anterior (TA) and diaphragm muscles were cryo‐sectioned (10 μm at −15°C) and succinate dehydrogenase (SDH) capacity was quantified as described by us previously 16,35 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…OCT‐covered gastrocnemius, tibialis anterior (TA) and diaphragm muscles were cryo‐sectioned (10 μm at −15°C) and succinate dehydrogenase (SDH) capacity was quantified as described by us previously 16,35 …”
Section: Methodsmentioning
confidence: 99%
“…Activity of citrate synthase (CS), an enzyme of the TCA cycle, was measured spectrophotometrically in gastrocnemius homogenates as described by us previously. 16,35 To complement assessment of SDH activity in muscle sections, activity of SDH/mitochondrial ETC complex II (CII) was assessed on isolated mitochondria from gastrocnemius muscles according to the manufacturer directions (Abcam, ab228560). Mitochondria were isolated as performed by us previously.…”
Section: Mitochondrial Enzyme Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…DMF is a potent immunoregulatory and anti-inflammatory and -oxidative drug via nuclear factor erythroid 2-related factor 2 (Nrf2) activation and hydroxycarboxylic acid receptor 2 (HCAR2) agonism (18). Our proof-of-concept study in the mdx mouse demonstrated short-term DMF treatment was more effective against key disease indices than SOC prednisone (PRED), including histopathology, muscle function, mitochondrial metabolism and disease driving gene signatures (19). In the present study, we aimed to evaluate moderate-term effects in mdx mice with an aggravated phenotype.…”
Section: Introductionmentioning
confidence: 91%
“…Our group is currently investigating the fumarate drug, DMF, for therapeutic application in DMD [ 59 ], and we are interested in comparing the risk–benefit profile of exogenous (via DMF) versus endogenous (via ASA) fumarate-induced Nrf2 targeting. For example, following 2 weeks oral treatment of DMF (100 mg/kg/day) and ASA (325 mg/kg/day), Nrf2 signaling was induced in DMF [ 60 ] but not ASA murine skeletal muscle (C57BL/10 wild-type (WT) and mdx ; unpublished results). Whereas, 8 weeks treatment via the oral route with a comparable dose did induce Nrf2 expression in mdx and WT skeletal muscle [ 14 ].…”
Section: Multi-functions Of Asa: a Deeper Perspectivementioning
confidence: 99%